E-052 Safety and efficacy of stenting post failed thrombectomy: multi-institutional experience. (4th August 2020) - Daou, B; Sweid, A; Koduri, S; Jabbour, P; Ringer, A; Kan, P; Rajah, G; Bining, M; Pandey, A
Abstract : Introduction: Even in the era of stent-retrievers, complete recanalization is often not achieved. Methods: In this multi-institutional effort, we retrospectively evaluated 101 consecutive patients across 6 centers who underwent placement of a self-expanding stent during thrombectomy, either as a rescue strategy for intracranial recanalization or for tandem extracranial/intracranial occlusion. We aimed to evaluate recanalization, complications, clinical outcomes, and antithrombotic regimens in these patients. Results: Occlusive thrombus was located in the internal carotid artery (ICA) in 23.8%, in the middle cerebral artery in 59.4% and in the vertebro-basilar circulation in 16.8% of cases. Indications for stenting included persistent occlusion/failed recanalization in 42.6% of cases, tandem occlusions with proximal flow limiting stenosis in 19.8%, vessel reocclusion after initial recanalization in 14.9%, vessel dissection in 15.8% cases, and underlying intracranial stenosis in 6.9% patients. 48.5% of patients had a stent deployed intracranially, 41.6% of stents were deployed within the extracranial ICA/vertebral artery while 9.9% extended from an extracranial to an intracranial vascular segment. Multiple stents were deployed in 9.9% of cases. Successful recanalization (TICI 2b/3) was obtained in 91.1% following stenting. Symptomatic intracranial hemorrhage occurred in 13 patients (12.9%), only two of which had received tPA. Significant in-stent stenosis/thrombosis occurred in 7 cases (6.9%). 54.9% had a favorable mRS score at 90 days (0–3) and 90-day mortality occurred in 15.8%. The primary factor associated with complications was placement of multiple stents (P=0.018). 71.3% of patients were loaded with antiplatelet agents intraoperatively prior to stent placement, most commonly with aspirin/Plavix ± eptifibatide or Tirofiban, followed by maintenance on dual antiplatelet treatment. There were no significant differences in outcomes between different antithrombotic regimens. Conclusion: Stent placement as a rescue strategy for thrombectomy failure and for tandem configurations offers a high rate of recanalization and favorable outcome without an increase in the hemorrhage risk regardless of antithrombotic regimen and tPA status. Disclosures: B. Daou: None. A. Sweid: None. S. Koduri: None. P. Jabbour: None. A. Ringer: None. P. Kan: None. G. Rajah: None. M. Bining: None. A. Pandey: None.